2018
DOI: 10.3389/fpubh.2018.00331
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Knowledge and Fear Levels of Breast Cancer With the Spiritual Characteristics of Nurses

Abstract: Introduction: Breast cancer is a common problem and it is important to understand the beliefs that increase awareness of breast cancer and guide early diagnosis behaviors. This research is planned to examine the knowledge and fear levels of breast cancer along with the spiritual characteristics of nurses.Methods: This is a descriptive type research. The domain of the research consists of women nurses working in Health Sciences University Samsun Education and Research Hospital. Sampling was not undertaken, rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…İnformation points in two studies conducted on the same scale in Turkey were detected to be moderate. [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] In other studies in which women's breast cancer knowledge levels were evaluated with different scales, it was stated that their knowledge level was moderate. 34-82-83-84-85-86-87 In two studies conducted on young women in Ethiopia, the breast cancer knowledge level of women was found as low.…”
Section: Discussionmentioning
confidence: 99%
“…İnformation points in two studies conducted on the same scale in Turkey were detected to be moderate. [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] In other studies in which women's breast cancer knowledge levels were evaluated with different scales, it was stated that their knowledge level was moderate. 34-82-83-84-85-86-87 In two studies conducted on young women in Ethiopia, the breast cancer knowledge level of women was found as low.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cal et al . [ 28 ] found that majority (71.9%) of the nurses in cancer care had experienced cancer fears during clinical practice. Similar findings had been reported over a decade ago by.…”
Section: Discussionmentioning
confidence: 99%